2005
DOI: 10.1634/stemcells.2004-0216
|View full text |Cite
|
Sign up to set email alerts
|

Rac2-Deficient Hematopoietic Stem Cells Show Defective Interaction with the Hematopoietic Microenvironment and Long-Term Engraftment Failure

Abstract: The hematopoietic-specific Rho GTPase, Rac2, regulates a variety of cellular functions including cell shape changes, motility, integrin-dependent adhesion, and apoptosis. In the study reported here, we demonstrate that wild-type (WT) hematopoietic stem cells/progenitors (HSC/P) preferentially engraft in nonablated Rac2 -/-bone marrow. In addition, primitive Rac2 -/-HSC/P transplanted into lethally irradiated WT recipients showed a significant competitive defect compared with WT cells. These defects appeared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 63 publications
0
42
0
Order By: Relevance
“…Similar findings were reported in Rac2-deficient HSC/P cells: the proliferation of Rac2 À/À HSC/P cells in high proliferative potential colonyforming assays was not different from their wild-type counterparts; however, in vivo studies demonstrated that Rac2 À/À HSC/P ability of long-term engraftment was impaired, suggesting that Rac2 plays an important role in HSC/P microenvironmental localization during the engraftment process. 51 In summary, the current studies provide evidence for the importance of FAK signaling in chemotactic and pro-adhesive responses of hematopoietic cells. We conclude that in vivo studies employing FAK-targeted mouse model systems are needed to provide insight into the function of FAK in various aspects of hematopoiesis, including HSC/P homing, engraftment and lineage development.…”
Section: Fak Deletion Significantly Reduces Cxcl12-mediated Migrationmentioning
confidence: 67%
“…Similar findings were reported in Rac2-deficient HSC/P cells: the proliferation of Rac2 À/À HSC/P cells in high proliferative potential colonyforming assays was not different from their wild-type counterparts; however, in vivo studies demonstrated that Rac2 À/À HSC/P ability of long-term engraftment was impaired, suggesting that Rac2 plays an important role in HSC/P microenvironmental localization during the engraftment process. 51 In summary, the current studies provide evidence for the importance of FAK signaling in chemotactic and pro-adhesive responses of hematopoietic cells. We conclude that in vivo studies employing FAK-targeted mouse model systems are needed to provide insight into the function of FAK in various aspects of hematopoiesis, including HSC/P homing, engraftment and lineage development.…”
Section: Fak Deletion Significantly Reduces Cxcl12-mediated Migrationmentioning
confidence: 67%
“…Other alternative conditioning regimens have been reported that involve mobilization using AMD3100, 44 which was sufficient for chimerism at levels of 5% overall chimerism using 4 ϫ 10 7 BM cells. Rac2 Ϫ/Ϫ mice could be modestly engrafted 45 at less than 5% overall using 2.5 ϫ 10 7 cells, but this was associated with mobilization that was most profound when both Rac1/2 were deleted. 46 An important observation of these studies is that STAT5 dosage regulates HSC competition.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Small Rho GTPases, including Rac1, Rac2, and Cdc42, are involved in the regulation of adhesion in various mammalian cell types, including hematopoietic cells. 40,[45][46][47] They act as molecular switches by cycling between an active GTP-bound form and an inactive GDP-bound form. Upon activation by distinct signals originating from these "environment sensing" receptors, active GTP-bound GTPases ultimately regulate actin polymerization, integrin clustering, and adhesion receptor-mediated adhesion.…”
Section: Increased Level Of Activation Of Cdc42 In Aged Primitive Hemmentioning
confidence: 99%